An evaluation of library services offered to preschoolers in selected private schools in Metro Manila with implications to preschool library standardization - Surla, Selina B. (School of Library and Information Studies, University of the Philippines Diliman, 2002)
The onset of the new millennium has brought about further advances in information technology. These are seen and felt by everyone, everywhere, and are most evident in the workplace and in the learning arena. These have, in fact, affected even the very young school children. Thus, it is not a surprise that preschools nowadays have their own libraries. However, with the DECS lacking recommended minimum preschool library standards, most preschools are having a difficult time setting-up libraries for their students.